Chapter 24 Introduction to the Section: Researching Ageism (2018)
In order to address ageism and potentially reduce its occurrence, it is essential to identify appropriate ways to research it. Ageism should be examined at the societal level and the individual level. It should be examined both explicitly and implicitly. Moreover, ageism is manifested towards others and towards one-self, thus both levels should be examined. Because ageism is manifested in the ways we think, feel and act towards age and ageing, all three domains should be assessed. Ageism has many theoretical grounds, which also should be incorporated when examining the phenomenon. This section presents both theoretical arguments and practical tools and best practices to facilitate research in the field of ageism. As international researchers, Wilińska, de Hontheim, and Anbäcken give a reflexive personal account of conducting research on ageism in different countries and cultures. They argue that being physically away from your own culture is an opportunity to re-examine common assumptions about age and ageing and develop a more critical understanding of these issues in light of their varied manifestations in different cultures. To some degree, this chapter corresponds with Snellman’s chapter (2018; chapter 25), as it indicates ways to broaden normative understandings of ageism through exposure to views and perspectives that do not represent the majority view in one’s own culture